GMJ 2019
DOI: 10.31661/gmj.v8i0.1296
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin-Loaded Chitosan Nanoparticles Improve Its Therapeutic Effects on Brucella-Infected J774A.1 Murine Cells

Abstract: Background: Final elimination of some intracellular bacterial agents, such as Brucella, is often a complex issue and impossible to achieve, primarily due to the presence and survival of the bacteria within phagocytic cells. By penetrating into the cell membrane, drug delivery nanosystems can reduce the number of intracellular bacteria. The aim of this study was to assess the efficacy of chitosan nanoparticles on the delivery of gentamicin into Brucella infected J774A.1 murine cells in vitro. Materials and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
(16 reference statements)
1
12
0
Order By: Relevance
“…Moreover, GM–AA–CSNPs showed prolonged release profiles over 60 h, allowing the release of 41%, 62%, or 80% of loaded drugs at pH 5, 6.4, and 7.5, respectively, which may provide a high blood concentration of GM and AA in vivo. Previous studies support our findings [ 15 , 30 ]. Interestingly, the infected wounds and bacterial infection-associated inflammation have acidic pH values [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, GM–AA–CSNPs showed prolonged release profiles over 60 h, allowing the release of 41%, 62%, or 80% of loaded drugs at pH 5, 6.4, and 7.5, respectively, which may provide a high blood concentration of GM and AA in vivo. Previous studies support our findings [ 15 , 30 ]. Interestingly, the infected wounds and bacterial infection-associated inflammation have acidic pH values [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…Chitosan nanoparticles were formulated, as described in our previous work, by ionic gelation method using sodium tripolyphosphate (TPP) (0.1%, v / v ) as a cross-linker [ 15 ]. In brief, a solution of chitosan (CS) of 200 mg in 100 mL acetic acid (2%, v / v ) was prepared.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CG0.5 and CG1 release around 90% of their payload over seven days, while CG2 releases 57.44 ± 2.72%. Previous studies attempting to control gentamicin release achieved 70% release over 8 h, with complete release by 24 h [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nanocarriers offer the potential for enhanced treatments by reducing drug buildup within cells and diminishing the necessary dosage and dosing frequency. Studies have indicated that nanoparticles can effectively prevent drug degradation while regulating drug delivery and encapsulation [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%